USING STORY MAPPING APPROACH TO IMPROVE READING NARRATIVE FOR JUNIOR HIGH SCHOOL - Lailatul Nikmah (Pusat Pengembangan Bahasa IAIN Tulungagung, 2012)
Although English has been taught in schools starting from elementary to junior high school levels, the fact shows that many student still difficult to read English texts. They may read fast but get nothing or they need a very long time to understand the texts. It means that they are not effective readers. It can be assumed that their comprehension skill is not good. Dealing with these phenomena, the teacher be given another technique to make their student to be effective readers. Because of that the teacher uses story mapping to solve the students’ problem. So we expect that this technique helps students to deepen their reading comprehension and ability to apply story mapping teaching strategies.